New response in electrochemical impedance spectroscopy due to the presence of molybdenum on AB5-type alloys - Díaz, Verónica (2015)
During the present investigation, it was observed that the inclusion of molybdenum in LaNi3.6Co0.7Mn(0.4-x)Al0.3Mox AB5-type alloys produced new responses in the electrochemical impedance spectroscopy (EIS) when they are used as an anode active material for Ni-MH batteries. The aim of this work is to study, using electrochemical impedance spectroscopy, the influence of molybdenum, on the performance of the electrode. EIS spectra were adjusted in terms of a physicochemical model of the dynamic response of the system. X ray diffraction and hydrogen diffusion coefficient calculated from discharges curves supported EIS model outcomes. The replacement of manganese by molybdenum, in a 2% w/w concentration level (AB5M1), has a positive effect for applications as energy storage material. In this sense, this alloy exhibits the lowest value of charge transfer resistance obtained from the analysis of impedance spectra. Moreover, changes in the (i0. aa) parameter, that is, the exchange current density and active area, respectively display a maximum value. The larger grade of fracture observed in AB5M1 can be due to the higher material´s fragility as a consequence of molybdenum incorporation. XRD analysis on the three alloys confirms this hypothesis as shown in the paper.